Ketriaditisan Konteks Pragmatik Tuturan Tidak Santun: Perspektif Kultur Spesifik - R. Kunjana Rahardi (Badan Pengembangan dan Pembinaan Bahasa, 2020)
The objective of this research was to describe the types of triadicities of pragmatic contexts on impolite utterances in the Indonesian language in culture-specific perspective. The research data were the natural utterances in a culture-specific domain intrinsically containing triadicity of pragmatic contexts. The data were collected and presented through the observation methods, both through the engaged conversation technique and uninvolved conversation technique. The data gathering techniques being applied in the observation method were the recording and note-taking techniques. In addition to the conversation technique, an interview technique was applied both the face-to-face and indirect conversations. The data gathering stage was completed when the data was ready to be analyzed. Data analysis was carried out using the identity method, especially the extralingual identity method. This aligned with the contextual analysis in pragmatics in which contextual aspects must be identified. The results of the study showedthat there were 10 types of triadicities of pragmatic contexts on impolite utterances in the Indonesian language in culture-specific perspective. They were triadicities of pragmatic contexts in: (1) pretense, (2) association, (3) taboos, (4) taunting, (5) arrogance, (6) pleonasm, (7) puns, (8) insults, (9) teasing, (10) interjection. The findings of research bring the significant contribution to the development of pragmatics, particularly the culture-specific pragmatics AbstrakTujuan penelitian ini adalah untuk mendeskripsikan tipe-tipe ketriaditisan konteks pragmatik dalam bahasa Indonesia dengan perspektif kultur spesifik. Data penelitian berupa tuturan-tuturan natural manusia dalam domain kultur spesifik yang secara implisit mengandung triadisitas konteks pragmatik tersebut. Data dikumpulkan dengan menerapkan metode simak, baik simak libat cakap maupun simak bebas libat cakap. Teknik pengumpulan data yang diterapkan adalah teknik catat dan teknik rekam. Selain teknik-teknik tersebut, diterapkan pula teknik wawancara, baik yang sifatnya semuka maupun tidak semuka. Tahap pengumpulan data dipandang selesai ketika data benar-benar telah siap untuk dianalisis. Selanjutnya, analisis data dilakukan dengan menerapkan metode padan, khususnya padan yang bersifat ekstralingual. Metode tersebut selaras dengan metode analisis kontekstual dalam pragmatik. Hasil penelitian menunjukkan bahwa terdapat 10 jenis ketriaditisan konteks pragmatik dalam bahasa Indonesia dalam perspektif kultur spesifik. Kesepuluh jenis tersebut adalah ketriaditisan konteks pragmatik dalam tuturan yang mengandung makna: (1) kepura-puraan, (2) asosiasi, (3) tabu, (4) ejekan, (5) kesombongan, (6) pleonasme, (7) lelucon, (8) hinaan, (9) godaan, (10) interjeksi. Temuan penelitian ini diyakini dapat memberikan kontribusi signifikan bagi pengembangan ilmu pragmatik, khususnya pragmatik dalam perspektif kultur spesifik.